Rheology based on suspension containing titanium dioxide - Alias, Hajar (2012)
Due to a high demand of an advanced in heat transfer application for an optimal plant performance, numerous researchers conducted research on heat transfer and flow behaviour of nanofluid in order to meet the expectation of the industry needs. However, there has been claimed that the stability and flow behaviour of nanofluid has become a drawback to its application in heat transfer enhancement. This research focuses on the determination of the rheological behavior of nanofluids when titania (TiO2) nanoparticles are suspended in deionized water. Nanofluid was formulated by using two-step method. The stability of nanofluid as a function of pH and surfactant were evaluated by using sedimentation method and FE-SEM was employed to analyze morphology of nanoparticles. From the results obtained, pH and surfactant affected the stability of nanofluid greatly. Based on rheology of nanofluids, behavior such as Newtonian and non-Newtonian behavior can be predicted. The rheological behaviour was observed to be affected by several main parameters which include temperature, concentration of titania, and concentration of surfactant. From this research, it was found that titania in deionized water exhibit non-Newtonian behaviour. Subsequently the viscosity of nanofluids was observed to be a function of particle loading, pH and temperature. All in all, the stability and rheological behaviour of nanofluid is proven not to be a disadvantage to the potential of nanofluid application